2019
DOI: 10.3390/e21040368
|View full text |Cite
|
Sign up to set email alerts
|

Using the Data-Compression Method for Studying Hunting Behavior in Small Mammals

Abstract: Using the data-compression method we revealed a similarity between hunting behaviors of the common shrew, which is insectivorous, and several rodent species with different types of diet. Seven rodent species studied displayed succinct, highly predictable hunting stereotypes, in which it was easy for the data compressor to find regularities. The generalist Norway rat, with its changeable manipulation of prey and less predictable transitions between stereotype elements, significantly differs from other species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…It turned out that complete (successful) hunting stereotypes in members of a natural ant colony are characterised by smaller complexity than incomplete hunting stereotypes in naive laboratory-reared ants. Together with similar results obtained later on rodents [ 21 , 34 ], this application of Kolmogorov complexity could help to distinguish between innate and learned components of behavioural stereotypes.…”
Section: Applying Ideas Of Information Theory For Comparative Analysi...supporting
confidence: 70%
See 1 more Smart Citation
“…It turned out that complete (successful) hunting stereotypes in members of a natural ant colony are characterised by smaller complexity than incomplete hunting stereotypes in naive laboratory-reared ants. Together with similar results obtained later on rodents [ 21 , 34 ], this application of Kolmogorov complexity could help to distinguish between innate and learned components of behavioural stereotypes.…”
Section: Applying Ideas Of Information Theory For Comparative Analysi...supporting
confidence: 70%
“…The first part of this review concentrates on applying information theory to the comparative analysis of stereotyped behaviours that enable animals to accomplish particular goals, such as chasing prey, avoiding a predator, or defending territories. The method of analysing ethological texts based on ideas of Kolmogorov complexity can serve many goals, from distinguishing between stereotyped and flexible parts of behaviours to understanding the evolutionary roots of complex stereotypes within animal lineages, such as rodents’ families [ 17 , 20 , 21 , 22 ]. The second part considers studying animal intelligent communication using an experimental approach based on Shannon entropy and Kolmogorov complexity [ 18 , 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…By regularity, we mean any characteristic of a text that makes it more predictable, such as frequency of occurrence of letters and sub-sequences and so on. With the use of this method, we revealed a surprising similarity between hunting behaviors of the common shrew, which is insectivorous, and several rodent species [24]. However, further behavioral observations showed that the modes of hunting could differ in different species.…”
Section: Introductionmentioning
confidence: 84%
“…To assign behavioral elements and obtain behavioral sequences, we applied The Observer XT 12.5 (Noldus Information Technology). In sum, we selected 19 behavioral elements (see Appendix A, Table A1, Video S1; details in: [22,24]). We assigned the letters to elements of behavior, in the order of their appearance, without taking into account their duration.…”
Section: Notions and Data Encodingmentioning
confidence: 99%
“…Unlike mammals or birds, in which entire orders differ primarily in the frequency and order in which they perform a shared set of behaviours (Reznikova et al, 2019;Winger, Barker, & Ree, 2014), even closely related snake species can differ greatly in the behaviours used (see Supplementary Material Video 1 for an overview of this diversity). This high behavioural diversity with little to no overlap in character states among species renders highly tailored ethograms broadly inapplicable across large clades.…”
Section: Quantitative Challenges Of Behavioural Analysis In Snakes and The Comparative Approachmentioning
confidence: 99%